Review of CaRP: CAPTCHA as Graphical Passwords - Pooja N. Sawarekar; Anuradha Salvi; Shilpa R. Bhoyar (Journal of Electronic Design Engineering, 2022)
For Different security purposes, many security systems are used now a day. For number of applications. Authentication is usually done with text-based passwords. The best alternative for text based password is graphical password. This paper is focuse on how to increase the security by using CAPTCHA technique with the graphical passcode. CAPTCHA: Completely Automated Public Turing test to tell Computers and Humans Apart is a technique to identify whether user is a human or a robot. To protect the website from bots CAPTCHA is used as image or a program ie computer generated program. As a graphical passcode, CAPTCHA: CaRP is focused on the CAPTCHA system. CaRP system is the combination of both graphical password and Captcha, it having advantages of both. So many security problems are solved by using this technic such as shoulder-surfing, relay, online guessing etc. CaRP also conquer the disbenifits of graphical passcode system. Mostly occured problem of graphical password is Image hotspot problem which is prevented in CaRP system. The CaRP method looks to integrate well with similar practical applications for improving internet security and delivers reasonable security and accessibility.